Digital Product Bundling as a Marketing Strategy for Home-Based Food SMEs: Evidence from Social Media Implementation in Indonesia - Nurcahyani, Adinda Fitri; Shafira, Fitria Riza; Lestari, Aprilia Qori Aina; Setiawati, Dian Murni (University Merdeka Malang, 2025)
This study examines the implementation of digital product bundling as a marketing strategy in a home-based food small and medium-sized enterprise (SME) in Indonesia. Using a descriptive qualitative approach, the research explores changes in marketing practices before and after the adoption of bundling strategies promoted through social media. Data were collected through in-depth interviews, observations, and focus group discussions with business owners and involved actors, and were analyzed using thematic analysis supported by a Planning of Action framework. The findings indicate that product bundling combined with social media marketing enhances product visibility, expands market reach, and strengthens consumer engagement through integrated offerings and improved packaging. However, the implementation also faces operational challenges, including production capacity constraints, labor limitations, and distribution inefficiencies. This study contributes to the literature on SME digital marketing by highlighting product bundling as a practical and adaptive strategy for home-based food enterprises in emerging economies. The results provide managerial insights for SMEs seeking to improve competitiveness through low-cost digital marketing strategies.